CONCERN Factorial Design Survey (FDS) Methods Test: Using REDCap as a Survey Platform - Garcia, Jose P. (Stud Health Technol Inform, 2019)
We assessed the feasibility of using REDCap as an FDS platform. REDCap lacks randomization and automation functionality, requiring the development of a workaround. A template survey was created containing all vignettes, copied for each survey instance and edited to hide unwanted content. REDCap configuration required three hours for forty-two surveys. The utilized “copy-and-hide” workaround was successful, providing quasi-automation and reasonable labor-time. Additional strategies are planned using REDCap’s Data Dictionary and other survey software.